Pengaruh Organizational Citizenship Behavior, Employee Engagement Dan Job Satisfaction Terhadap Job Performance Di Koa D’surfer HotelCanggu-Bali - I Putu Yogi Anto Wijaya; I Made Sunata (Universitas Triatma Mulya, 2024)
Efforts to improve OCB, employee engagement, job satisfaction and job performance are things that companies must attention. The present study endeavors to ascertain the following: 1) the effect of organizational citizenship behavior on job performance at Koa D'Surfer Hotel; 2) the effect of employee engagement on job performance at Koa D'Surfer Hotel; 3) the effect of job satisfaction on job performance at Koa D' Surfer Hotel; 4) the identification of independent variables that exert the most significant influence on job performance at Koa D'Surfer Hotel; and 5) the extent to which organizational citizenship behavior, employee engagement, and job satisfaction to job performance at Koa D’Surfer Hotel. The method of research used is a quantitative method with a sample 52 employees. The sampling technique is a saturated sample. The analysis techniques used are research instrument tests, classical assumption tests, multiple linear regression analysis, t-test, beta coefficient and determination analysis. The results this research show that the regression model Y = 4.962 + 0.234X1 + 0.269X2 + 0.141X3. The research findings indicate that: 1) job performance is direct and real impacted by OCB; 2) job performance is direct and real impacted by employee engagement; 3) job satisfaction is direct and real impacted by job performance; and 4) the organizational citizenship behavior variable has a significant impact on job performance. This is demonstrated by the standardized coefficients beta value of the organizational citizenship behavior variable, which is 0.452; employee engagement is 0.418; and job satisfaction is 0.202. 5) Of the variables that influence work performance, 71,3% are related to OCB, employee engagement, and job satisfaction and 28,7% are influenced by variables not included in this research.